Measuring The Accomodation of Sharia Principles in Determining the Pricing of Consumer Financing Products of BSM (Sharia Mandiri Bank) - Syaparuddin Syaparuddin (Al-Ulum, 2017)
This study is intended to evaluate the pricing determination of consumer financing products of BSM, so that the customers can find out if BSM provides a treatment of installment payments on consumer financing products in accordance with sharia principles. In establishing the pricing on consumer financing products, BSM uses two methods, namely: the annuity method and the proportional (flat) method. The Construction of pricing on the consumer financing products in BSM is based on: (a) the total of installment payment per-month, it is based on financing platfond, percentage of margin, and period of time, (b) the principal installment payment per-month, it is based on total of principal installment payment per-month, and margin, (c) the installment payament of profit margin per-month, it is based on platfond, principal, and percentage of margin. The pricing used by BSM needs to be revitalized because (a) there is a profit return factor for customers, (b) containing a gharar element, and (c) using the paradigm of conventional bank in setting pricing.